Local News and Community Belonging: The Role of Local Media in Fostering Social Cohesion - Zhang, Ruiqi (International Journal of Social Sciences and Public Administration, 2025)
This paper will examine the role of local news stories in enhancing member's feelings of belonging and identity in the context of a multicultural community, and the integral role that local news plays in the promotion of social cohesion. Local news can provide a space to promote the voice of different ethnicities and cultures when covering local news stories in the community, and in doing so, local communities can mitigate cultural divides, encourage cross cultural dialogue, and foster ways to work together in ordinary spaces. Furthermore, recognition of cultural diversity helps to both solidify respect and recognition for minorities and enrich the cultural ecology of communities. Despite the important work local news can do in promoting social cohesion in multicultural communities, their capabilities are being affected by economic pressures, digital transformation, and media bias. At the same time, how to explore the constraints on local news in promoting autonomy (independence) and credibility (trust) in today's media environment has become increasingly important. Thus, the pursuit of the literatures coverage of social inclusion and local news, placement of storytelling in the community is an irreplaceable role of local news. Future research may look to examine how to improve communication structures (reporting design) in local news and how to engage multicultural communities for support purposes in order to promote active social inclusion of communities and individual members' identity.